Romero [videorecording (DVD)] - Duigan, John, 1949-; Julia, Raul; Jordan, Richard, 1937-1993; Alicia, Ana (1989)
Romero is the true story of the Catholic Archbishop Oscar Romero who lived in El Salvador during the political unrest in the 1970s. The government launched a 'terror campaign' against the guerillas in an attempt to crush them. Archbishop Romero's protests against the government's actions was perceived as disloyalty. As an example to others, the government began to destroy churches and murder priests. Despite persecution, Romero continued to speak out against the atrocities the government was committing against the people of El Salvador, until his assassination.